Common Fixed Point Theorems of the Asymptotic Sequences in Ordered Cone Metric Spaces - Chi-Ming Chen (Journal of Applied Mathematics)
We introduce the notions of the asymptotic SMK-sequence with respect to the stronger Meir-Keeler cone-type mapping ξ:int(P)∪θ→[0,1) and the asymptotic WMK-sequence with respect to the weaker Meir-Keeler cone-type mapping ϕ:int(P)∪θ→int(P)∪θ and prove some common fixed point theorems for these two asymptotic sequences in cone metric spaces with regular cone P. Our results generalize some recent results.